Orbital floor reconstruction with high density polyethylene - Daniel Pozza (2010)
Surgical interventions in blow out fractures are generally indicated in cases of alterations in orbital function (e.g. diplopia)and for aesthetic reasons (e.g. enophthalmos). In assessing the severity of the injury, the clinician often uses parameterssuch as changes in visual acuity, patient-reported diplopia, changes in globe position and evaluation of the extraocularmuscles in association with imaging exams. Computed tomography has been the modality of choice for detailed imagingdiagnosis and surgical planning of orbital trauma. High density polyethylene may be successfully used in orbital floorreconstruction to restore function and esthetics. Taking into account the follow up of six months, the availability and theadvantages of high density polyethylene implants, it can be concluded that their use in reconstruction of orbital floordefects is a good choice.